2021
DOI: 10.47102/annals-acadmedsg.2021134
|View full text |Cite
|
Sign up to set email alerts
|

Parental perception and guideline awareness of children’s lifestyle behaviours at ages 5 to 14 in Singapore

Abstract: Introduction: There are limited data on the descriptive lifestyle behaviour of school-age children in Singapore. Methods: A total of 100 parents of children ages 5 to 14 participated in a parents’ proxy-reported survey. Frequency of moderate physical activity (PA) and vigorous PA was assessed, while t-tests or chi-square test was used to examine differences between weekdays and weekends for sleep, screen viewing time (SVT) and sedentary behaviour (SB). Results: Of the 100 children (68% of Chinese ethnicity, 59… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Parental perception of their child’s weight, calorie intake, PA, SVT exposure and sleep were assessed with the questions previously published [ 25 ] “Do you think your child is …”, with the response options of “Overweight”, “Normal weight”, “Underweight” and “Not sure”. The other 3 questions were (1) “Do you feel that your child receives an adequate amount of physical activity to benefit his/her growth, development and health?”; (2) “Are you concerned about the amount of recreational screen time your child is currently exposed to?”; and (3) “Do you think your child is getting adequate sleep to support his/her growth, development and health?”, with response options of “Yes”, “No” and “Not sure”.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental perception of their child’s weight, calorie intake, PA, SVT exposure and sleep were assessed with the questions previously published [ 25 ] “Do you think your child is …”, with the response options of “Overweight”, “Normal weight”, “Underweight” and “Not sure”. The other 3 questions were (1) “Do you feel that your child receives an adequate amount of physical activity to benefit his/her growth, development and health?”; (2) “Are you concerned about the amount of recreational screen time your child is currently exposed to?”; and (3) “Do you think your child is getting adequate sleep to support his/her growth, development and health?”, with response options of “Yes”, “No” and “Not sure”.…”
Section: Methodsmentioning
confidence: 99%
“…Parental perception of their child's weight, calorie intake, PA, SVT exposure and sleep were assessed with the questions previously published [25] "Do you think your child is . .…”
Section: Parental Perception Of Child's Healthmentioning
confidence: 99%
“…Almost one-third (32%) and 43% of children in the cited study did not participate in any moderate and vigorous physical activity in a typical week, respectively. More children had lesser than the recommended duration of night-time sleep (8 hr/day) on weekday (18.8%) than on weekend (2.1%) (Quah et al, 2021) The other local study that collected time use data of the same lifestyle behaviours is by Chia and colleagues albeit for younger children aged 5 years and below (Chia et al, 2020). The findings from Quah and colleagues' study suggested that lifestyle behaviours were sub-optimal in a sizeable proportion of children in Singapore which then spurred the development of The Singapore Integrated 24-hour Activity Guidelines for Children and Adolescents (Loo et al, 2022).…”
Section: Physical Activity Sedentary Behaviour and Sleep Among Singap...mentioning
confidence: 96%
“…The questionnaire comprised three segments: (a) demographic characteristics of parent and child; (b) children's PA using 9 questions adapted from the short form International Physical Activity Questionnaire (IPAQ-SF) [22] which records the activity of four intensity levels: (1) vigorous-intensity activity such as aerobics, (2) moderate-intensity activity such as leisure cycling, (3) walking, and (4) sitting; (c) children's sleep habits (night-time sleep and day-time napping) adapted from the Child Sleep Habits Questionnaire [23]; (d) children's recreational screen viewing time (SVT) was captured as the average time a child spends on a screen [24] (e) Parental perception of child' health and awareness of lifestyle guidelines for children. Details of the questionnaire items have been reported previously [25]. The questionnaire was developed to assess caregiver-reported child's PA in a week, sleep habits, SB, and SVT on a weekday and on the weekend where the caregivers were asked to recall their child's habitual movement behaviours in a typical 7-day week.…”
Section: Survey Instrument and Mode Of Data Acquisitionmentioning
confidence: 99%
“…The questions used to assess parental perception of children's health and awareness of activity guidelines for children and adolescents were previously published [25].…”
Section: Parental Perception and Awareness Of Child Health And Moveme...mentioning
confidence: 99%